1991
DOI: 10.1007/bf00159982
|View full text |Cite
|
Sign up to set email alerts
|

The lysis of Gram-negative Alcaligenes eutrophus by enzymes from Cytophaga

Abstract: The use of Cytophaga lysing enzymes was investigated for the liberation of poly-~-hydroxybutyrate (PHB) granules from the Gram-negative bacterium AlcaIigenes eutrophus. Complete cell lysis was approached within a 60 minute period. Contrary to previous findings for the lysis of Gram-negative bacteria, prior removal of the outer membrane was not essential for enzymic lysis. The destabilisation of the outer membrane by the removal of divalent cations resulted in no significant improvement in the disruption proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…System variables affecting homogenizer disruption efficiency include suspension temperature, homogenizer operating pressure, number of homogenizer passes (Hetherington et al, 1971), and homogenizer valve design (Keshavarz-Moore et al, 1990). Cell concentration is reported to have no discernible influence on cell-disruption efficiency over a wide range of cell-concentrations and operating pressures (Hetherington et al, 1971;Brookman, 1974;Btischelberger and Loncin, 1989;Agerkvist and Enfors, 1990;Harrison et al, 1991), with few studies contradicting this (Sauer et al, 1989;Middelberg et al, 199 1).…”
Section: Introductionmentioning
confidence: 96%
“…System variables affecting homogenizer disruption efficiency include suspension temperature, homogenizer operating pressure, number of homogenizer passes (Hetherington et al, 1971), and homogenizer valve design (Keshavarz-Moore et al, 1990). Cell concentration is reported to have no discernible influence on cell-disruption efficiency over a wide range of cell-concentrations and operating pressures (Hetherington et al, 1971;Brookman, 1974;Btischelberger and Loncin, 1989;Agerkvist and Enfors, 1990;Harrison et al, 1991), with few studies contradicting this (Sauer et al, 1989;Middelberg et al, 199 1).…”
Section: Introductionmentioning
confidence: 96%
“…The grinding process generates heat which is counter balanced by circulating cooling water surrounding the chamber. Although the alkaline pretreatment of cells containing PHA granules enhances single-pass disruption in a high-pressure homogenizer, full protein release requires at least two passes [ 108 ]. To improve single-pass disruption, substances such as 0.1% SDS, sodium chloride, potassium chloride, lysozyme, EDTA, or mixtures of these can be employed [ 109 ].…”
Section: Extraction Of Phamentioning
confidence: 99%
“…Pretreatments with lysozyme, EDTA, and combination of the two, were seen to improve single pass disruption relative to untreated material (Harrison et al, 1991c). In further work with enzymes, Harrison et al (1991a) reported essentially complete lysis of A. eutrophus cells upon treatment (37.5°C, pH 7.3, 60 min) with lytic enzymes of Cytophaga sp without any mechanical processing. But lytic enzymes (e.g., hen lysozyme) are generally too expensive for commercial scale processing.…”
Section: Reviewmentioning
confidence: 99%